New Assay Procedure for Separation of Mycoplasmas from Virus Pools and Tissue Culture Systems - Zgorniak-Nowosielska, Izabella (1967)
Presence of mycoplasma organisms in tissue culture systems and virus pools was detected by titration of the contaminated material on agarose-suspended BHK21/13S cells. The use of this method permitted isolation of mycoplasmas which could not be detected by standard assay methods. Mycoplasma colonies at concentrations ranging from 10(4) to 10(6) colony-forming units/ml in agarose-BHK21/13S media could be distinguished from virus plaques, and the two populations of microorganisms could be easily disassociated either by electron microscopy or by biological methods. All isolated mycoplasmas were identified in growth inhibition tests as belonging to the GDL group. The growth inhibition test on agarose-BHK21/13S cell suspension plates could also be applied directly to those strains which could not be isolated by standard assay procedures.